Sistem Pendukung Keputusan Penerimaan Karyawan Menggunakan Metode WASPAS dengan Pembobotan Metode ROC - Sinaga, Ferdinan Ganda Saputra; Simamora, Burju Francisko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In a company, hiring the best employees is quite important, as it can affect the level of profit or loss experienced by a company. This has led company management to make every effort to determine the best employees in order to make the right choice. Therefore, the author will create a decision support system that can be used as a reference in hiring the best employees. The method used in this study is the WASPAS (Weight Agregate Sum Product Assessment) method with ROC (Rank Order Centroid) weighting. By applying these two methods, it is hoped that the best possible results will be obtained in determining the best employees to hire. Based on this issue, a Decision Support System (DSS) needs to be developed to support the employee selection process, by applying the WASPAS method with ROC method weighting. The WASPAS method is a method that can reduce errors or optimize estimations for selecting the highest and lowest values. Thus, the main objective of the MCDM approach is to select the best option from a set of alternatives in the face of conflicting criteria. The ROC method is based on the level of importance or priority of the criteria, and the ROC technique assigns weights to each criterion according to the ranking assessed based on the level of priority. In this study, the method applied to generate the best employee acceptance decision is the Weight Aggregated Sum Product Assessment (WASPAS) with ROC method weighting. This method was chosen because it is a decision support model where the main tool is a functional hierarchy with the main input being human perception, in this case, experts in the field or those who understand the issues of selecting the best employees at CV Sihol Pardomuan.